Modulation Imaging Contrast Agent for Cancer - Fawwaz, Muammar (Pharmaceutical Reports, 2024)
Molecular imaging, also known as molecular imaging, is a medical technique used to visualize and analyze biological molecules in the human or animal body. According to the Society of Nuclear Medicine and Molecular Imaging's website, "Molecular Imaging" is a type of medical imaging that provides a detailed picture of what is happening in the body at the molecular and cellular levels. This definition refers to the significant advancements researchers have made over the past two decades in applying the principles of molecular imaging in various areas, from basic and translational science to advanced patient diagnosis and therapy. Essentially, molecular imaging allows us to visualize biochemical processes and target localization patterns that are invisible at the level of anatomical imaging. The goal of molecular imaging is to obtain information about molecular activity and function in living tissue. The technologies commonly used in imaging modulation are Positron Emission Tomography (PET), Single Photon Emission Computed Tomography (SPECT), and Magnetic Resonance Imaging (MRI).